Temps: The Many Faces of the Changing Workplace - Vosko, Leah F. (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "Temps: The Many Faces of the Changing Workplace," by Jackie Krasas Rogers.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Temporary employment